The Evaluation of Coronary Artery Disease in Patients with Silent Cerebral Infarction - Kader Kırkan; Pelin Pınar; Pınar Çe; Reha Bilgin; Muhteşem Gedizlioğlu (Türk Nöroloji Dergisi, 2010)
OBJECTIVE: While there are many records of silent cerebral infarction in patients with coronary artery disease, there is no study about coronary artery disease in patients with silent cerebral infarction. Therefore, we intended to evaluate coronary artery disease in patients without history of stroke or transient ischemic attack but with silent cerebral infarction on cranial magnetic resonance imaging by noninvasive methods. METHODS: Coronary artery disease was investigated by means of routine laboratory tests (glucose, urea, total cholesterol, low density lipoprotein, high density lipoprotein), electrocardiography, Carotid Doppler ultrasonography, echocardiography, treadmill effort test, and myocardial perfusion scintigraphy when needed. The patient and the control groups were compared for coronary artery disease statistically. RESULTS: Twenty-five male and 15 female patients with silent cerebral infarction on cranial magnetic resonance imaging and 15 healthy male and 10 healthy female volunteers were recruited in this study. The mean age was 66.7 in the patient group and 63.84 in the control group. Silent cerebral infarction was established as multiple in 34 (85%) patients and single in 6 (15%) patients. Coronary artery disease was determined in 7 patients in the patient group (1 female, 6 males) and in none in the control group (p= 0.03). CONCLUSION: Our study showed that coronary artery disease is an important risk factor in patients with silent cerebral infarction. Detection of silent cerebral infarcts are important, as they may lead to examination and treatment of the patients cardiologically